Comparative analysis of the surface interaction properties of the binding sites of CDK2, CDK4 and ERK2 - Kelly, M.; Mancera, Ricardo (Wiley-VCH Verlag GmbH & Co. KGaA, 2006)
Recently developed hydrogen-bonding and hydrophobic analysis algorithms were used to investigate the interaction properties of the ATP binding sites of CDK2, CDK4, and ERK2. We were able to prioritise those hydrogen-bonding groups that are observed to bind the native ATP ligand, as well as to identify other important groups found to bind inhibitors of these enzymes. However, as the hydrogen-bonding groups in the ATP binding sites of these enzymes are fairly well-conserved, we have confirmed that inhibitor selectivity may be predominantly due to differences in either the hydrophobic or steric properties of their binding sites. In particular, the hydrophobic properties of regions outside the specificitysurface were observed to provide a rationale for the difference in specificity between various inhibitors to these enzymes. Our method was thus able to identify variations in hydrophobicity. The greater hydrophobicity of certain regions of CDK4 over analogous regions in CDK2 was detectable; likewise, it was possible to distinguish variations in hydrophobicity for regions of CDK2 against those in ERK2, despite the fact that these regions are largely composed of similar residue types.